Preparation and Characterization of Solid-Supported Lipid Bilayers Formed by Langmuir-Blodgett Deposition A Tutorial - Kurniawan, James (Langmuir : the ACS journal of surfaces and colloids, 2018)
The structure, phase behavior, and properties of cellular membranes are derived from their composition, which includes phospholipids, sphingolipids, sterols, and proteins with various levels of glycosylation. Because of the intricate nature of cellular membranes, a plethora of in vitro studies have been carried out with model membrane systems that capture particular properties such as fluidity, permeability, and protein binding but vastly simplify the membrane composition in order to focus in detail on a specialized property or function. Supported lipid bilayers (SLB) are widely used as archetypes for cellular membranes, and this instructional review primarily focuses on the preparation and characterization of SLB systems formed by Langmuir deposition methods. Typical characterization methods, which take advantage of the planar orientation of SLBs, are illustrated, and references that go into more depth are included. This invited instructional review is written so that nonexperts can quickly gain in-depth knowledge regarding the preparation and characterization of SLBs. In addition, this work goes beyond traditional instructional reviews to provide expert readers with new results that cover a wider range of SLB systems than those previously reported in the literature. The quality of an SLB is frequently not well described, and details such as topological defects can influence the results and conclusions of an individual study. This article quantifies and compares the quality of SLBs fabricated from a variety of gel and fluid compositions, in correlation with preparation techniques and parameters, to generate general rules of thumb to guide the construction of designed SLB systems